Plant community structure and nitrogen inputs modulate the climate signal on leaf traits. Issue 10 (October 2017) - Borgy, Benjamin; Violle, Cyrille; Choler, Philippe; Denelle, Pierre; Munoz, François; Kattge, Jens; Lavorel, Sandra; Loranger, Jessy; Amiaud, Bernard; Bahn, Michael; van Bodegom, Peter M.; Brisse, Henry; et al.
Abstract: Aim: Leaf traits strongly impact biogeochemical cycles in terrestrial ecosystems. Understanding leaf trait variation along environmental gradients is thus essential to improve the representation of vegetation in Earth system models. Our aims were to quantify relationships between leaf traits and climate in permanent grasslands at a biogeographical scale and to test whether these relationships were sensitive to (a) the level of nitrogen inputs and (b) the inclusion of information pertaining to plant community organization. Location: Permanent grasslands throughout France. Methods: We combined existing datasets on climate, soil, nitrogen inputs (fertilization and deposition), species composition and four traits, namely specific leaf area, leaf dry matter content and leaf nitrogen and phosphorus concentrations, for 15, 865 French permanent grasslands. Trait–climate relationships were tested using the following four climatic variables available across 1, 833 pixels (5 km × 5 km): mean annual temperature (MAT) and precipitation (MAP), and two indices accounting for the length of the growing season. We compared these relationships at the pixel level using either using community‐level or species' trait means. Results: Our findings were as follows: (a) leaf traits related to plant nutrient economy shift consistently along a gradient of growing season length accounting for temperature and soil water limitations of plant growth (GSLtw ); (b) weighting leaf traits by species abundance in local communities is pivotal to capture leaf trait–environment relationships correctly at a biogeographical scale; and (c) the relationships between traits and GSLtw weaken for grasslands with a high nitrogen input. Main conclusions: The effects of climate on plant communities are better described using composite descriptors than coarse variables such as MAT or MAP, but appear weaker for high‐nitrogen grasslands. Using information at the community level tends to strengthen trait–climate relationships. The interplay of land management, community assembly and bioclimate appears crucial to the prediction of leaf trait variations and their effects on biogeochemical cycles.